Antibody-Dependent Cellular Cytotoxicity (ADCC)-Mediating Antibodies Constrain Neutralizing Antibody Escape Pathway - Mielke, Dieter (Front Immunol, 2019)
Both neutralization and antibody-dependent cellular cytotoxicity (ADCC) may be required for effective protection against HIV-1 infection. While there is extensive information on the targets of early neutralizing antibody (nAb) responses, much less is known about the targets of ADCC responses, which are more difficult to characterize. In four individuals recruited during acute HIV-infection, ADCC responses were detected 3–7 weeks prior to nAb responses. To determine the relative influence of ADCC and nAb responses on virus evolution, we performed an in-depth investigation of one individual (CAP63) who showed the highest nAb and ADCC responses. Both nAbs and ADCC antibodies targeted the V4 region of the Env, although there were some differences in epitope recognition. We identified accelerated viral evolution in this region concurrent with emergence of nAb activity, but not ADCC activity. Deep sequencing demonstrated that most nAb escape mutations were strongly selected for, however one nAb escape mutation that rendered the virus highly susceptible to autologous ADCC responses, was suppressed despite not affecting viral fitness. This escape mutation also rendered the virus more sensitive to autologous responses, as well as monoclonal antibodies targeting CD4-induced epitopes, compared to the wildtype virus. In conclusion, ADCC responses and nAbs in donor CAP63 recognized overlapping but unique epitopes in the V4 region, and while ADCC activity was present prior to nAbs, it did not drive viral evolution during this time. However, ADCC responses may select against nAb escape pathways that expose other common ADCC epitopes thereby restricting viral replication and expansion.